The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fcell.2021.606890
|View full text |Cite
|
Sign up to set email alerts
|

Post-Adipose-Derived Stem Cells (ADSC) Stimulated by Collagen Type V (Col V) Mitigate the Progression of Osteoarthritic Rabbit Articular Cartilage

Abstract: Collagen is essential for cartilage adhesion and formation. In the present study, histology, immunofluorescence, morphometry, and qRT-PCR suggested that adipose-derived stem cells (ADSCs) stimulated by type V collagen (Col V) induce a significant increase of type II collagen (Col II) in the degenerative area of surgical-induced osteoarthritic rabbit articular cartilage (OA). In vitro, the effects of Col V on the proliferation and differentiation of ADSC were investigated. The expression of the cartilage-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…Some ECM molecules reported to modulate MSC differentiation are also observed in MSC spheroids. Upregulation of collagen V, 99 laminin, 100 and perlecan 101 was seen in MSC spheroids; in 2D studies, these ECM molecules respectively were seen to promote chondrogenesis, neurite outgrowth, and osteogenesis while blocking adipogenesis. Interestingly, collagen IV, which in 2D studies is upregulated during adipogenic induction, is less expressed in 3D MSC spheroid cultures.…”
Section: D Msc Culture Modulates Ecm Molecules: Implications For Line...mentioning
confidence: 93%
“…Some ECM molecules reported to modulate MSC differentiation are also observed in MSC spheroids. Upregulation of collagen V, 99 laminin, 100 and perlecan 101 was seen in MSC spheroids; in 2D studies, these ECM molecules respectively were seen to promote chondrogenesis, neurite outgrowth, and osteogenesis while blocking adipogenesis. Interestingly, collagen IV, which in 2D studies is upregulated during adipogenic induction, is less expressed in 3D MSC spheroid cultures.…”
Section: D Msc Culture Modulates Ecm Molecules: Implications For Line...mentioning
confidence: 93%
“…Therefore, tissue adhesion should also be considered. In addition, Cruz et al [44] found that Collagen V stimulated adipose stem cells induced a significant increase in Col II in areas of osteoarthritic articular cartilage degeneration, improved cell distribution and actin fiber structure during the initial stages of chondroblast differentiation, and promoted adhesion. Understanding the mechanisms by which new tissues adhere to native cartilage is crucial, making biomaterials more likely to be used to treat osteoarthritic lesions.…”
Section: Proteinsmentioning
confidence: 99%
“…To enhance the therapeutic efficacy of ADSCs against knee OA, it is essential to maintain the viability of ADSCs within the joint cavity. Various methods have been developed to prolong the survival of stem cells at the site of administration, including the use of spheroid culture techniques [ 12 , 13 ] and improvement of the culture medium [ 14 , 15 ]. Among these methods, microspheres have recently emerged as a highly promising culture tool [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%